2017
DOI: 10.1038/s41598-017-03836-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of ascorbic acid in the cerebrospinal fluid of cognitively intact elderly patients with major depression: a preliminary study

Abstract: Major depressive disorder (MDD) in the elderly is a risk factor for dementia, but the precise biological basis remains unknown, hampering the search for novel biomarkers and treatments. In this study, we performed metabolomics analysis of cerebrospinal fluid (CSF) from cognitively intact elderly patients (N = 28) with MDD and age- and gender-matched healthy controls (N = 18). The CSF levels of 177 substances were measured, while 288 substances were below the detection limit. Only ascorbic acid was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…More importantly, the results in the presence of both VC and TBHQ were identical to those with TBHQ alone, indicating no interference with the detection of CoQ10H 2 and CoQ10. Levels of VC in human CSF are reported to be about 200 µM, (14) and we confirmed this observation. 200 µM VC in CSF corresponds to 50 µM VC in the extraction solvent.…”
Section: Resultssupporting
confidence: 89%
“…More importantly, the results in the presence of both VC and TBHQ were identical to those with TBHQ alone, indicating no interference with the detection of CoQ10H 2 and CoQ10. Levels of VC in human CSF are reported to be about 200 µM, (14) and we confirmed this observation. 200 µM VC in CSF corresponds to 50 µM VC in the extraction solvent.…”
Section: Resultssupporting
confidence: 89%
“…In this study, natural Vit C intake seems to be beneficial for depression, but Vit C from dietary supplements has no effect [36]. This implicates that various supplements have influence on depression or being influenced by depression [32][33][34][35][36].…”
Section: The Role Of Supplements In Depressive Disordermentioning
confidence: 57%
“…Rakofsky et al undertook a literature search on PUFA, Vit C, NAC, inositol, folic acid, and citicholine and found inconsistent correlation between PUFA, Vit C, and citicholin and bipolar disorder, no correlation between folic acid, choline and cytidine-PUFA and bipolar disorder [34]. Hashimoto et al also found significantly (p = 0.0029) higher levels of Vit C in the cerebrospinal fluid CSF of elderly people with depression, but no cognitive decline in comparison with healthy controls [35]. The elevation was interpreted as a result of increased oxidative stress in the central nervous system.…”
Section: The Role Of Supplements In Depressive Disordermentioning
confidence: 98%
“…This database contains the retention indices and two MRM transitions of each of the 475 endogenous metabolites which facilitate simple, fast, and reliable metabolite identification and semi-quantification. This strategy has been successfully applied to many studies ( Hashimoto et al, 2017 ; Nishiumi et al, 2017 ; Tomonaga et al, 2018 ). Metabolites existing in the real samples but not in blank samples or metabolites in real samples with peak areas at least fivefold as high as that in blank samples were selected for further data analysis.…”
Section: Methodsmentioning
confidence: 99%